2022
DOI: 10.1093/intqhc/mzac063
|View full text |Cite
|
Sign up to set email alerts
|

Trends of in-hospital and ICU mortality in COVID-19 patients over the fourth and fifth COVID-19 surges in Iran: a retrospective cohort study from Iran

Abstract: Background The current study aimed to investigate the temporal trend of in-hospital and ICU mortality of COVID-19 patients over 6 months in the spring and summer of 2021 in Iran. Methods We performed an observational retrospective cohort study on 14,355 patients who were hospitalized with confirmed COVID-19 for six months from April to September 2021 in Qazvin province, Iran. The trend of overall in-hospital mortality and ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Fever, cough, and dyspnoea were the most prevalent symptoms of the SARS CoV-2 among the hospitalized children in this study, and our findings were supported by the previous studies conducted on children or adults [ 17 , 28 , 29 ]. Our study found dyspnoea as the only symptom associated with a higher risk of death.…”
Section: Discussionsupporting
confidence: 91%
“…Fever, cough, and dyspnoea were the most prevalent symptoms of the SARS CoV-2 among the hospitalized children in this study, and our findings were supported by the previous studies conducted on children or adults [ 17 , 28 , 29 ]. Our study found dyspnoea as the only symptom associated with a higher risk of death.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the overall in-hospital mortality and ICU mortality were 12.33% and 39%, respectively. The high in-hospital mortality rate may be related to the increased severity of illness in ICU admission, i.e., patients who received non-invasive respiratory support were likely to stay out of the ICU due to low ICU capacity, and more patients requiring intubation were admitted, and this has led to an increase in both in-ICU and out-ICU mortality, as well as an increase in overall in-hospital mortality ( 15 ).…”
Section: Discussionmentioning
confidence: 99%